Real time analytics with SAP HANA : enhance your SAP HANA skills using this step-by-step guide to create data models and reports for real time analytics /: enhance your SAP HANA skills using this step-by-step guide to create data models and reports for real time analytics. (2015) - Singh, Vinay
No abstract available